2017
DOI: 10.1037/xlm0000332
|View full text |Cite
|
Sign up to set email alerts
|

More than just beliefs: Experience and beliefs jointly contribute to volume effects on metacognitive judgments.

Abstract: Experience-based cues, such as perceptual fluency, have long been thought to influence metacognitive judgments (Kelley & Jacoby, 1996; Koriat, 1997). Studies found that manipulations of perceptual fluency via changes in font and volume alter Judgments of Learning (JOLs) without influencing memory performance (Rhodes & Castel, 2008, 2009). Nonetheless, recent research (Mueller, Tauber, & Dunlosky, 2013; Mueller, Dunlosky, Tauber, & Rhodes, 2014, 2016) has challenged the notion that experience-based cues such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 48 publications
4
103
2
Order By: Relevance
“…given that evidence has revealed a direct-albeit small-impact of processing fluency on JOLs that cannot be attributed to beliefs (e.g., Besken, 2016;Besken & Mulligan, 2014;Susser & Mulligan, 2015;Undorf & Erdfelder, 2015). This conclusion is also supported by evidence from Frank and Kuhlmann (2017), who found that most of their participants believed that they would remember more loud words than quiet words, which was also evident in their JOLs. Most important, some participants did not hold the volume belief, yet volume still had an impact on their JOLs analogous to the participants who did show such a belief.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…given that evidence has revealed a direct-albeit small-impact of processing fluency on JOLs that cannot be attributed to beliefs (e.g., Besken, 2016;Besken & Mulligan, 2014;Susser & Mulligan, 2015;Undorf & Erdfelder, 2015). This conclusion is also supported by evidence from Frank and Kuhlmann (2017), who found that most of their participants believed that they would remember more loud words than quiet words, which was also evident in their JOLs. Most important, some participants did not hold the volume belief, yet volume still had an impact on their JOLs analogous to the participants who did show such a belief.…”
Section: Discussionmentioning
confidence: 82%
“…One potentially relevant dimension is the intensity or strength of the belief (cf. Frank & Kuhlmann, 2017). According to this intensity hypothesis, strongly held beliefs are sufficient to impact JOLs, whereas weakly held beliefs are less so.…”
Section: Explaining the (Minimal) Impact Of Beliefs About Aging On Jolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment 4 provides more evidence for theory-based processes, as participants produced higher JOLs for truth than for lies, despite the lack of objective response latency differences. Third, participants can be directly asked about their beliefs through questionnaires without being exposed to the experimental materials (Besken, 2016;Koriat et al, 2004;Kornell et al, 2011;Mueller et al, 2014;Susser et al, 2016), make JOLs before they are exposed to the specific episode on an item-by-item basis (Mueller et al, 2014(Mueller et al, , 2016, or make global estimations about the predicted memory performance before the experiment begins (Frank & Kuhlmann, 2016). Experiment 5 showed the contribution of a priori beliefs to JOLs through the presentation of a scenario, in which participants had to predict their memory performance without exposure to the experiment, revealing higher memory predictions for truth trials than lie trials.…”
Section: Discussionmentioning
confidence: 99%
“…An important recent concern in metacognition is the extent to which participants' judgments are influenced by their expectations (Efklides, ; Kornell & Finn, ). For example, Frank and Kuhlman () compared metacognition and memory across spoken words that were presented at a loud, or soft, volume. Although memory was not affected by volume, people who expected loud voices to affect memory consistently gave higher JOLs to items that were presented in a loud voice, thereby supporting the view that beliefs affect individual metacognitive judgments.…”
Section: The Hypervigilance Hypothesis and Placebo Groupsmentioning
confidence: 99%